Host-directed short-term missions: interviews with Japanese liaisons - Barber, Ron (Missiology, 2015)
This article focuses on the viewpoint and activities of Japanese cultural liaisons who host short-term mission (STM) groups from the United States to Japan. The hosts’ description of their experiences in planning, financing, orienting, and ministering with STM groups shows a willingness of some Japanese to work with STM but also a frustration when their contributions in these areas are minimized by their STM guests. Based on my interviews with Japanese liaisons, I suggest that movement toward a host-directed approach to STM built upon listening to the hosts, thinking long-term, developing cultural awareness, and emphasizing relationships can promote a more missiologically responsible and effective partnership between STM guests and their hosts.